Being in the teaching laboratory: explorations of material agents in student learning - Rie Malm (Dansk Universitetspaedagogisk Tidsskrift)
The laboratory has long been conceptualised as central for learning science in higher education. Students are provided with possibilities to learn content, develop skills, and thereby gain confidence working in a laboratory. However, the unchallenged assumption is that students simply learn from being in and doing laboratory work. This study argues for including a socio-material lens to explore in greater detail how and what students learn from materials and being in the laboratory as well as showing underlying power dynamics as it manifests in the teaching laboratory. To develop this argument, the article offers a qualitative study of instructors’ notions of students’ laboratory-based learning. Grounded in discourse analysis, I explore instructors’ sense making of learning in intersection with socio-material analysis to capture understandings of entanglements of learning with and from materials in the laboratory space.